Guava in Dentistry: A Potent Transition from Traditional to Modern Medicine in Oral Health - Sultana, Ayesha; Aleemuddin, Mohammad; Hussain, Md. Sadique; Mustafa, Mohammed; Maqbool, Mudasir (Current Bioactive Compounds, 2025)
Psidium guajava or guava is a plant that contains a variety of bioactive compounds that have been used to treat oral and dental issues. The plant is unique and traditional, with a wide range of therapeutic uses. Guava's healing and medicinal effects have been reported through clinical trials, laboratory studies, and surveys. Over 3.5 billion people worldwide suffer from oral disorders, such as dental caries, periodontal disease, plague, gum inflammation, toothache, tooth loss, and oral cancer. The World Health Organization (WHO) advocates for affordable, safe, and environmentally friendly oral hygiene products to combat the high cost of treatment for oral illnesses. Guava tree parts, including roots, leaves, bark, stem, and fruits, are used to treat dental ailments, like halitosis, bleeding gums, gingivitis, periodontal conditions, dental caries, toothache, and mouth cancers. Phytochemicals, with their properties, have been proven effective in treating and managing systemic and dental diseases. Guava, a rich source of varied phyto-constituents, effectively combats oxidative stress, thereby preventing the deterioration of oral health. The translation of Psidium guajava from traditional medicine to modern medicine can be a boon to cost-effective and potent treatment in managing oral health and dental disorders.
Keywords: periodontal disease